Prevalence of reproductive diseases and its associated risk factors in crossbred dairy cows (Research in Agriculture Livestock and Fisheries, 2015)
Reproductive diseases of crossbred dairy cows significantly reduce productivity which is of great concern of dairy producers worldwide. The objectives of this study were to determine the prevalence of reproductive diseases and its associated risk factors in crossbred dairy cows in selected areas of Bangladesh. The study was conducted at eight villages of Ullapara Upazila under Sirajganj district. A total of 197 dairy farms having 488 breedable crossbred dairy cows (395 cows + 93 heifers) were randomly selected. A questionnaire as well as examination of cows was made to collect data on occurrence of reproductive diseases. The overall prevalence of reproductive diseases was 39.4%. Among the diseases, post calving anoestrus was 8.6%, delayed puberty was 6.8%, repeat breeding was 5.7%, retained placenta was 4.7%, metritis was 3.9%, dystocia was 3.3%, vaginal prolapse was 2.7%, abortion was 2.1% and uterine prolapse was 1.6%. The body condition score (BCS) of cows significantly (P0.05) the occurrence of reproductive diseases in crossbred dairy cows. In conclusion, further studies are needed with more number of cows to confirm the findings DOI: http://dx.doi.org/10.3329/ralf.v1i1.22357 Res. Agric., Livest. Fish.1(1): 71-79, Dec 2014